In a pit with a lion on a snowy day - Batterson, Mark. (Sisters, Or. : Multnomah Publishers, 2006)
Make sense of the "random" pieces of life. Get a God's-eye perspective, and get answers to questions about unexplained experiences. Readers will discover that they've been in the right place at the right time, every time.
Locking eyes wth your lion -- The odd thing about odds -- Unlearning your fears -- The art of reframing -- Guaranteed uncertainty -- Playing it safe is risky -- Grab opportunity by the mane -- The importance of looking foolish -- Unleash the lion chaser within.
Includes bibliographical references (p. [175]-182) .
Keywords: Bible -- Criticism, interpretation, etc; Benaiah -- (Biblical figure)